Selective feeding and foreign plastid retention in an Antarctic dinoflagellate. Issue 6 (3rd November 2014) - Sellers, C. Grier; Gast, Rebecca J.; Sanders, Robert W.; Graham, L.
<x xml:space="preserve">Abstract</x> The peridinin‐containing plastid found in most photosynthetic dinoflagellates is thought to have been replaced in a few lineages by plastids of chlorophyte, diatom, or haptophyte origin. Other distinct lineages of phagotrophic dinoflagellates retain functional plastids obtained from algal prey for different durations and with varying source species specificity. 18S rRNA gene sequence analyses have placed a novel gymnodinoid dinoflagellate isolated from the Ross Sea (RSD) in the Kareniaceae, a family of dinoflagellates with permanent plastids of haptophyte origin. In contrast to other species in this family, the RSD contains kleptoplastids sequestered from its prey, Phaeocystis antarctica. Culture experiments were employed to determine whether the RSD fed selectively on P. antarctica when offered in combination with another polar haptophyte or cryptophyte species, and whether the RSD, isolated from its prey and starved, would take up plastids from P. antarctica or from other polar haptophyte or cryptophyte species. Evidence was obtained for selective feeding on P. antarctica, plastid uptake from P. antarctica, and increased RSD growth in the presence of P. antarctica. The presence of a peduncle‐like structure in the RSD suggests that kleptoplasts are obtained by myzocytosis. RSD cells incubated without P. antarctica were capable of survival for at least 29.5 months. This remarkable longevity of the RSD's kleptoplasts and its species specificity for prey and plastid source is consistent with its prolonged co‐evolution with P. antarctica. It may also reflect the presence of a plastid protein import mechanism and genes transferred to the dinokaryon from a lost permanent haptophyte plastid.